Trajectory Planning of Time Optimal Manipulator based on Complex Method - Han Chen; Linsheng Li (Jixie chuandong)
At present， the operate time of the most manipulators are not optimally during the working process. In order to improve the working efficiency of the manipulator， a time optimal manipulator trajectory planning method based on the complex method is proposed. The method of 5-7-5 polynomial interpolation method is taken as the basis of trajectory planning， the motion angle， motion velocity and motion acceleration are taken as constraint， the optimization is carried out by using the complex method， the time optimal motion trajectory that meets the motion requirements is obtained. The FS20N robot is used as the object for research and analysis， and imported into MATLAB for verification， the simulation structure shows that the complex method effectively optimizes the time.